Dualism Of Halal Fatwa Institutions On The Self-Declare Mechanism - Magfiratun, Siti; Awaludin, Muhammad (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2025)
Halal Product Guarantee in Indonesia has gone through various of regulation changes starting from KMA No. 518 and 519 of 2001 to Law No. 33 of 2014 then updated in the cluster of law No. 11 of 2020 on Job Creation and most recently is Government Regulation no. 39 of 2021 as the basis for the halal certification self-declaration mechanism for micro and small enterprises (MSEs). However, this rule change and creates the impression of dualism institution between the Fatwa Committee and MUI Fatwa Commission in the process of determining the halal fatwa of a product. So this paper focuses on the study of institutional dualism in issuing halal fatwa statements on the halal certification self-declaration mechanism. This research is classified as a library study (library research) with the main source a document of Himpunan Hasil Ijtima' Ulama Fatwa Commission throughout Indonesia VIII -2024. The results of this study show that the existence of the Fatwa Committee in the self-declaration mechanism makes institutional dualism in issuing halal fatwa. Where previously halal fatwa was only issued by MUI then certified by BPJPH.